PAI Teacher's Strategy in Developing Students' Morals at MTS Negeri 1 Pemalang Year 2023/2024 - Rosyada, Nada Aqila; Inayati, Nurul Latifatul (ISTAWA, 2023)
The development of technology has a negative impact, one of which is in behavior, personality or morals. Morals at this time have decreased. Therefore, there is a need for moral guidance carried out both at home and at school, one of which is MTs Negeri 1 Pemalang. The scope of this research is to find out the theory of moral development, the strategies used by PAI teachers in moral development at MTs Negeri 1 Pemalang, and the supporting and inhibiting factors of moral development at MTs Negeri 1 Pemalang. The method used is a method with qualitative mapping by conducting field observations, interviews and documentation in data collection. The results of the research that has been done are that teachers use direct and indirect strategies. And there are supporting and inhibiting factors in implementing moral coaching. Supporting factors are facilities and infrastructure, teacher experience and extracurricular activities while inhibiting factors come from family, environment, self, and technological advances that are misused.